Dismorfia Muscular y su relación con síntomas de Trastornos de la Conducta Alimentaria - Rosario Castro López (Revista Mexicana de Trastornos Alimentarios, 2013)
One of the diseases that arouses increasing interest in the health field is the Muscle Dysmorphia (MD), which is why through this study will analyze your relationship with eating behavior disorders (ED) in athletes. The sample consisted of 154 athletes who routinely perform bodybuilding exercise, which were subjected to two self-administered test to measure your levels of muscle Dysmorphia (Adonis Complex) and their scores on ED test through the EDI-2. The results show statistically significant relationships (r = .47 p <.001) between the variable significant muscle Dysmorphia test many of TCA dimensions, a fact that confirms the link between both disorders. Also obtained through regression analysis TCA dimensions demonstrated predictors of the study variable, explaining them as a whole 28% of the variability of muscle Dysmorphia.